(untitled) (International Journal of Banking and Finance, 2009)
This paper provides empirical evidence on the role of fundamentalists and technicians in the Chinese stock market. Three econometric models are used to differentiate the stock price effect between the actions of traders who act on the basis of fundamental analysis and those acting on the basis of technical analysis. The models are estimated using randomly selected monthly and daily data on the stock prices of one hundred companies listed on the Shanghai Stock Exchange. The results reveal that both fundamentalists and technicians have roles to play in stock price formation, although technicians appear to play a more important role. This result holds even if the government intervention is allowed for. Some explanations are presented for the dominance of technicians.